2013
DOI: 10.1128/aem.03160-12
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Intermediate Sulfur Species in Biological Reduction of Elemental Sulfur under Acidic, Hydrothermal Conditions

Abstract: The thermoacidophile and obligate elemental sulfur (S 8 0 )-reducing anaerobe Acidilobus sulfurireducens 18D70 does not associate with bulk solid-phase sulfur during S 8 0 -dependent batch culture growth. Cyclic voltammetry indicated the production of hydrogen sulfide (H 2 S) as well as polysulfides after 1 day of batch growth of the organism at pH 3.0 and 81°C. The production of polysulfide is likely due to the abiotic reaction between S 8 0 and the biologically produced H 2 S, as evinced by a rapid cessation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 49 publications
3
66
0
Order By: Relevance
“…With the nanoparticles themselves soluble and neutrally charged, we propose that these may diffuse through the cellular lipid membrane and act as a cytoplasmic terminal electron acceptor for the upregulated NSR‐like enzyme. A similar mechanism of S 0 reduction through dialysis tubing was described for Acidilobus sulfurireducens , where the authors also showed that the growth rate of sulfur nanoparticles, and thus the size distribution, was influenced by the pH of the medium as well as presence of organic carbon (Boyd and Druschel, ).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…With the nanoparticles themselves soluble and neutrally charged, we propose that these may diffuse through the cellular lipid membrane and act as a cytoplasmic terminal electron acceptor for the upregulated NSR‐like enzyme. A similar mechanism of S 0 reduction through dialysis tubing was described for Acidilobus sulfurireducens , where the authors also showed that the growth rate of sulfur nanoparticles, and thus the size distribution, was influenced by the pH of the medium as well as presence of organic carbon (Boyd and Druschel, ).…”
Section: Discussionmentioning
confidence: 68%
“…However, it has been shown that direct attachment is not necessary for growth by Pyrodictium brockii (Kelly, 1990), which still grows with bulk sulfur sequestered by dialysis tubing. Similarly, the ability to grow without direct access to sulfur was demonstrated in Acidolobus sulfurireducens (Boyd and Druschel, 2013) and in Acidianus sp. strain DS80 (Amendabar and Boyd, 2018).…”
Section: Growth Under Different Electron Accepting Conditionsmentioning
confidence: 80%
“…Considering the conditions analyzed in this study, with polysulfide expected to be present in concentrations of circa of 0.1 mM at pH 6.5, and the presence of planktonic cells despite the dialysis membrane, it is reasonable to hypothesize that polysulfide can act as an electron acceptor for D. amilsii at pH 6.5. In the pH 3.5 culture, polysulfide is expected at very low concentration (in the order of pM), but nanosulfur particles less than 6–8 kDa could have been formed from elemental sulfur as it was shown for A. sulfurireducens (Boyd and Druschel, ). Nanosulfur particles would be able to diffuse through the dialysis membrane and become available for respiration by D. amilsii .…”
Section: Discussionmentioning
confidence: 74%
“…Potential elemental sulfur disproportionation by Caldimicrobium relatives in the deepest sediment layers is also consistent with the high sulfate porewater concentrations measured in the same sediment horizons (Figure 2). Presence of these potential metabolisms only in hydrothermal sediments was therefore likely due to the hydrothermal context where substrates for these activities were generated by abiotic reactions allowed in high temperature conditions (Von Damm et al, 1985;Boyd and Druschel, 2013). These metabolisms could therefore provide additional sulfate and sustain Archaeoglobales metabolism, mainly based on sulfate or iron reduction (Brileya and Reysenbach, 2014), as well as the other potential sulfate reducing lineages identified in these sediments (e.g., GBG/HotSeep-1, SEEP-SRB, Desulfatiglans relatives, etc.…”
Section: Hydrothermal Influence Leads To Contrasted Microbial Communitymentioning
confidence: 99%